Ultra-Broadband For All In Europe: Can Access Regulation Hinder Innovation And Welfare Maximisation? - Giovanni Battista Amendola (International Telecommunications Society (ITS), 2015)
Most of the European countries risk not reaching the 2020 Digital Agenda for Europe (DAE) targets. In order to achieve these targets, private investments in ultra-broadband networks should be vigorously promoted by access regulation whilst the deployment of ultra-broadband networks in unprofitable areas should be subsidized by means of appropriate public funding. Fiber to the Cabinet (FTTC) is considered a key technology in order to reach the 2020 DAE targets. This deployment model is widely adopted in a number of countries including, among others, Germany, the UK and Italy. The paper addresses FTTC regulation both at national and local level, that is in geographic areas subsidized by State aids. First, it emerges a clear trade-off at national level between the goal of infrastructure-based competition at the cabinet level and the achievement of the 2020 DAE targets. Inappropriate access regulation may indeed jeopardize the 2020 DAE targets by decreasing private investors' incentives to roll out FTTC networks, as well as to deploy new technologies such as Vectoring. Access regulation may thus, rather paradoxically, increase the amount of State aid funding which is required in a given country to meet the 2020 DAE targets. Second, excessive access obligations in geographies subsidized by State aids can also substantially increase State aid funding and, thus, undermine the capability of a given country to reach the 2020 DAE targets.
Keywords: 330